2015
DOI: 10.1016/j.anr.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-esteem Improvement Program on Self-esteem and Peer Attachment in Elementary School Children with Observed Problematic Behaviors

Abstract: The self-esteem improvement program in this study improved the self-esteem and peer attachment in elementary school children. The self-esteem program helped acknowledge the peer's name and increased their connections. The program needs to be considered as a formal and consistent program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
2
8
0
5
Order By: Relevance
“…The findings of the present study suggest that the experimental group showed a statistically significant decrease in anxiety and depression scores, and an increase in self-esteem scores ( P < 0.001) over the 6-mo interval, indicating that the psychosocial intervention had a positive impact on the children. These findings are supported by previous studies which showed similar outcomes[ 32 - 36 ]. In this context, a recent study by Haugland et al [ 37 ] found that school-based CBT delivered by a school nurse was effective in reducing the anxiety among adolescents[ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study suggest that the experimental group showed a statistically significant decrease in anxiety and depression scores, and an increase in self-esteem scores ( P < 0.001) over the 6-mo interval, indicating that the psychosocial intervention had a positive impact on the children. These findings are supported by previous studies which showed similar outcomes[ 32 - 36 ]. In this context, a recent study by Haugland et al [ 37 ] found that school-based CBT delivered by a school nurse was effective in reducing the anxiety among adolescents[ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…The meta-analysis of Lee et al (2013) convincingly argued that promoting the protective processes might be more effective than decreasing risk processes factors in facilitating resilience. Programs for decreasing disturbances in positive self-resources and enhancing self-esteem and self-compassion, such as self-esteem improvement programs and mindful self-compassion programs, have the potential to interrupt the long-lasting effects of child maltreatment on adulthood subjective well-being (Bluth & Eisenlohr-Moul, 2017; Park & Park, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Respecto de aquellos estudios con resultados positivos, vale la pena resaltar la intervención desarrollada por Soriano y Franco (2010), en donde un componente adicional y transversal al programa es el entrenamiento en mindfulness o conciencia plena. Asimismo, es importante anotar que estos programas se desarrollan de forma presencial mediante talleres teórico-prácticos (Aciego de Mendoza et al, 2003;Barón, 2012;Leiva et al, 2015;Park & Park, 2015;Sánchez et al, 2019;Soriano & Franco, 2010;Uribe et al, 2016;Vera et al, 2010), aunque en uno de ellos se destaca la figura de las mentorías (Marino et al, 2020). Finalmente, respecto al momento más oportuno, se han llevado a cabo intervenciones posteriores a la jornada escolar (Park & Park, 2015) o durante esta (Barón, 2012), buscando asegurar la asistencia de los participantes.…”
Section: Introductionunclassified